DO HOTS CORRELATE WITH READING COMPREHENSION? - Endah Ariani (Language-Edu, 2021)
The intent of the research is whether there is correlation between HOTS and RC. The researchs’ design is correlation design that this study was projected to give the respon of these questions,” Is there a correlation between HOTS and RC?” The participants who took part in this study are 140 students. The instruments of the research were tests which were needed to gather the data. These participants had to do two tests. The first test was the analysis, synthesis, and evaluation.The second test was literal comprehension and inference comprehension. The HOT skills Assesment was ten questions to analysis, seven questions to synthesis and eight questions to evaluation. And reading comprehension test was 12 items of multiple choices for literal comprehension and 12 items of multiple choices for inference comprehension. Total numbers of correct answer from these instruments were calculated. To get the purpose of the study, those numbers of correct answer were being correlated using Bivariate Pearson in SPSS 20.The result of the research showed the positive relationship between HOT skills and RC. The coefficient correlation is r-value .552. It means that the significant relationship between these two variables was a fair and answers the hypothesis that the Ho is rejected because the significance level is lower than 0.05 (p value 0<005) and H1 is accepted because the significance level is more than 0.05 (p value 0>005).This suggestions to other research are to increase the study in exploring sharper and deeper concerning with teaching and assessing methodology in senior high school since critical thinking has been given in high school curricula. Moreover, the study also suggests to further research to not only verify the theory that has been known but also to conduct introspective study and to develop study in investigating and exploring factors of how the students can be critical thinkers and how teacher guides students to be critical thinkers, also improve book which include critical thinker.Keywords:  HOTS, Critical Thinking and RC